(untitled) (The Strategic Review for Southern Africa, 2020)
As the title indicates this publication is the third issue in a series of reviews. The first issue was subtitled 2010: Development or decline? (2010) and the second was New paths, old promises? (2011). These publications are edited in the Department of Sociology at Wits University as part of its Strategic Planning and Allocation of Resources Committee (SPARC) Programme. The series is intended to be a revival of the South African Review edited by the South African Research Service and published by Ravan Press in the 1980s and early 1990s. Arguably one of the best known of these series was issue seven edited by Steven Friedman and Doreen Atkinson, The Small Miracle: South Africa's negotiated settlement (1994). The latest publication should also be seen as direct competition for the Human Sciences Research Council's (HSRC) regular publication, State of the Nation. The New South African Review 3 is organised into four parts, namely Party, Power and Class; Ecology, Economy and Labour; Public Policy and Social Practice; and South Africa at Large. The four editors introduce each of the sections, consisting of 16 chapters in total. Thebook's format appears to be that of a yearbook but it is not linked to a specific year. It is therefore not in the same category as for example the South African Institute of Race Relations' annual South Africa Survey. The Review is organised around a theme, albeit very general in its formulation, and in the case of the third issue it is also not applicable to all its chapters. At the same time, though, it is not a yearbook as the choice of chapters and their foci are on the latest developments.